2019
DOI: 10.2109/jcersj2.18170
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation and mineralization of strontium-substituted hydroxyapatite coating on magnesium alloy synthesized via hydrothermal route

Abstract: Magnesium (Mg) and its alloy as promising biodegradable orthopaedic implants have gained immense attention by virtue of their superior biocompatibility and mechanical compatibility. In order to increase the long-term corrosion resistance of Mg and its alloys in clinical application, in this work, a series of strontium-substituted hydroxyapatite (SrHA) coatings were constructed on Mg alloy via hydrothermal route. These SrHA coatings possessed bilayer structure with flower-like clusters as the surface layer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Obviously, the corrosion rate of AZ91 in the culture medium was greater than that in PBS. Meanwhile, compared with Mg alloy samples without the environment of CO 2 incubator, the mass loss of our samples was much smaller. , …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Obviously, the corrosion rate of AZ91 in the culture medium was greater than that in PBS. Meanwhile, compared with Mg alloy samples without the environment of CO 2 incubator, the mass loss of our samples was much smaller. , …”
Section: Resultsmentioning
confidence: 73%
“…As is well known, the degradation of magnesium can make the surrounding environment alkaline, and the pH of the immersion solution was more than 10 without surface treatment. 23,24 The abnormality, decrease, and small vibration of pH on the 4th day may have originated from the addition of CO 2 . Then, the pH of the immersion solution increased slowly on the 7th day for A group (the red line shown in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sr 2+ expands the HAp unit cell and increases the cell volume because it has a larger ionic radius than Ca 2+ (112 vs. 99 pm). The Sr-low HAp wettability and strong Sr concentration would provide good corrosion resistance for metallic substrates [90].…”
Section: Cationic Substitutions In Hap Coatingsmentioning
confidence: 99%
“…Recent studies have shown that surface modifications by coatings prepared on magnesium alloys can improve corrosion resistance in the humoral environment effectively. There are some preparation methods that are usually used, such as the hydrothermal method [6][7][8], the sol-gel method [9][10][11], microwave treatment [12], chemical conversion treatment [13,14], micro-arc oxidation [15], anodization [16], plasma spraying [17], the dip coating method [18], electrophoretic deposition [19,20], the laser deposition technique [21], the biomimetic method [22], etc. Due to its lower temperature of reaction, making it easy to prepare dense and uniform coating, hydrothermal method is considered as one of the best ways to prepare coatings among these methods.…”
Section: Introductionmentioning
confidence: 99%